President's Message: What’s in the Future for ORNAC? - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1992)
The time is here again to make sure everyone is informed as to the issues, current activities and future projects that ORNAC Executive, Board and Commit- tees are actively working on.